Effect of Number of Spermatozoa, Oviduct Condition and Timing of Artificial Insemination on Fertility and Fertile Period of Kampung Rooster Spermatozoa - Saleh, DM; Sugiyatno, Sugiyatno; Mugiyono, S; Siswadi, RW (ANIMAL PRODUCTION, 2012)
Abstract. This study was carried out to determine the optimum fertility and fertile period using the number of spermatozoa, oviduct condition and timing of insemination of native rooster spermatozoa. Ninety six commercial Isa brown pullets and nine kampung roosters were used in this study in a 3Ã2Ã2 factorial arrangement with one bird in a cage constituting a unit. The factor levels were the number of spermatozoa (50, 100 and 150 million/0.1 ml), oviduct condition (hard-shelled eggs and free hard-shelled eggs), and timing of artificial insemination (in the morning, at 7 AM and in the afternoon, at 4 PM).Â  The results showed that among the treatments there was no significant interaction to fertility and fertile period. Insemination with 50 million sperm number seemed to be the same result with the other 2 treatments. Oviduct condition had a highly significant difference on fertility and fertile period percentage, and timing of insemination did not differ between morning and afternoon.Â  In conclusion, the only oviduct condition (free hard-shelled eggs) was the best results for insemination in terms of fertility and fertile period of native roosters.Â  It is recommended that for the maximum fertility and fertile period, hens should be inseminated with 50 million spermatozoa, free of hard-shelled eggs and insemination performed in the morning or in the afternoon.Â Keywords: timing of artificial insemination, fertility, fertile period, semen dose, oviduct conditionAnimal Production 14(1):32-36, January 2012